Soccer - Brown, Jonatha A. (Milwaukee, WI Weekly Reader Early Learning Center, 2005)
Describes the history, objectives, exciting plays, and championships as well as the rules on the field.
5 - 9
Keywords: Soccer; My Favorite Sport